Reptiles in the Pontianak and Kubu Raya Residental Area, West Kalimantan, Indonesia - Anandita Eka Setiadi; HANUM MUKTI RAHAYU (Society for Indonesian Biodiversity, 2021)
Abstract. Setiadi AE, Rahayu HM. 2021. Reptiles in the Pontianak and Kubu Raya Residental Area, West Kalimantan, Indonesia. Biodiversitas 22: 2763-2770. The increase in population is directly proportional to housing needs. Expansion of residential areas can threaten the diversity of reptiles in West Kalimantan. This study aims to inventory and identify the diversity of reptiles in residential areas in Pontianak and Kubu Raya, West Kalimantan province, Indonesia. This research gives a better understanding of reptilian urban species to support monitoring and evaluation of biodiversity in West Kalimantan. This research uses the descriptive exploratory method. Four study areas were selected based on a proportion of impervious surfaces. Data collection used the VES (Visual Encounter Survey). Identification refers to Reptile field guides and identification books. The data were analyzed descriptively qualitatively, the level reptile diversity was analyzed using the Shannon Diversity Index, and the similarities of reptiles between the residential area in Pontianak and Kubu Raya were assessed using the Jaccard similarity coefficient. The results showed, from 50 individual reptiles found in Pontianak and Kubu Raya, there were 13 reptile species from the order Squamata and the order Testudines. The Shannon-Wiener Diversity Index of 2.26 and Jaccard similarity coefficient 0.384, indicating that the level of diversity of reptile species in the two study areas is classified as moderate.